Assessment of Body Mass Index for Obesity Diagnosis in the Mexican Population: A Cross-Sectional Analysis - Jorge Alejandro Ayala San Pedro; Dylani Rosa Avila Salcedo; Livia Magdalena Martínez Borja; Elizabeth Castillo Montufar (Obesities, 2025)
The diagnosis of obesity is conventionally determined by the Body Mass Index (BMI), with a threshold of 30 being extensively accepted. However, the validity of this cutoff point is subject to variation due to ethnic differences, and its accuracy in the Mexican population remains unvalidated. This cross-sectional, observational, and analytical study endeavored to assess the diagnostic performance of BMIs ≥ 30 in comparison to body fat determination using bioimpedance. A total of 715 Mexican adults, aged over 18 years were analyzed. Anthropometric measurements, including weight, height, and BMI, were recorded, and body fat percentage was assessed. The results showed that BMIs ≥ 30 had a sensitivity of 62.4%, a specificity of 93.9%, a positive predictive value (PPV) of 95.5%, and a negative predictive value (NPV) of 54%. In contrast, a BMI cut-off of ≥27 demonstrated superior diagnostic performance, with a sensitivity of 81.3%, specificity of 82.5%, PPV of 90.8%, and NPV of 67.3%. The chi-square test revealed a significant difference in obesity diagnosis between bioimpedance and BMIs ≥ 30 (p < 0.05). These findings suggest that the current BMI cutoff of ≥30 underestimates obesity diagnosis, while a cutoff of ≥27 may provide a more accurate diagnostic threshold, emphasizing the necessity for population-specific adjustments.